A New Black Elderberry Dye Enriched in Antioxidants Designed for Healthy Sweets Production - Dżugan Małgorzata; Pizoń Aleksandra; Tomczyk Monika; Kapusta Ireneusz (MDPI AG, 2019)
The aim of the study was to obtain a dye from black elder fruits and flowers and to study their potential in production of jellies with high antioxidant activity. Three dyes were produced by lyophilization of aqueous extracts: (1) fruits dye (F), (2) flowers dye (FL), and (3) fruits and flowers dye (F + FL). Their polyphenol profiles were compared by means of ultra-performance liquid chromatography (UPLC). The antioxidant activity [ferric reducing/antioxidant power assay (FRAP) and DPPH radicals scavenging test and total phenolics were compared by spectrophotometric methods. Jellies were produced from agar and gelatin with the addition of three obtained dyes, and their antioxidant water- and lipid soluble fractions were tested with a Photochem device. Results indicated that black elder fruits are rich in anthocyanins, especially cyanidin-3-O-sambubioside (7.56 mg/g d.w.), while flowers are rich in polyphenols, especially chlorogenic acid (2.82 mg/g d.w.) and rutin (4.04 mg/g d.w.). FL dye exhibited higher antioxidant activity compared to F dye (for about 30−40%), regardless of the used method, whereas F + FL dye was characterized by intermediate antioxidant activity. Jellies produced with the addition of FL dye had better antioxidant properties but unattractive color and unpleasant taste, but the use of F + FL dye created a product of favorable organoleptic properties and antioxidant activity comparable to jellies with F dye addition.